Progressive collapse behaviour of earthquake-damaged interior precast concrete joints with headed bars and plastic hinge relocation - Nguyen, Van Hung (2024)
This study investigated progressive collapse behaviour of earthquake-damaged interior precast concrete (PC) joints with headed bars. The main objective was to quantify the impact of slight and moderate earthquake damage on their residual collapse resistance. The research began with a numerical investigation to understand the interaction between a 2D frame's global response to seismic loading and its local response during a threat-independent progressive collapse event. Additionally, a separate set of numerical studies examined interior PC joints under cyclic loading to determine maximum drift ratio demands, yielding 2.5% for slightly and 3.5% for moderately damaged joints. Subsequently, an experimental programme under quasi-static loading conditions was conducted on five interior PC joints under cyclic loading, followed by progressive collapse resistance tests. Test results indicated that damaged joints exhibited flexural and catenary action during progressive collapse, but compressive arch action could not be mobilised due to residual cracks from the initial cyclic loading phase. Comparing damaged joints to fully intact ones from a companion study revealed deterioration in stiffness and deformation capacity during a subsequent progressive collapse, with degree of severity proportional to the extent of damage sustained in the cyclic loading phase. Relative to the intact joints without being subjected to cyclic loading, moderately damaged specimens exhibited a degradation of 63% in stiffness and 38% in deformation capacity, compared to slightly damaged specimens, which showed reductions of 38% in stiffness and 28% in deformation capacity. In contrast, strain hardening of steel bars in both slightly and moderately damaged specimens led to slightly greater collapse resistance than the intact joints. Additionally, failure mode shifted from ductile fracture to premature pull-through failure of headed bars in moderately damaged specimens. In this regard, in post-earthquake progressive collapse assessment, it is recommended to use maximum crack width thresholds of 0.2 to 1.0 mm for slight damage and 1.0 to 2.0 mm for moderate damage.